A weekly‐diary study of students' schoolwork motivation and parental support. (31st July 2022) - Wu, Yao; Hilpert, Peter; Tenenbaum, Harriet; Ng‐Knight, Terry
Abstract: Background: Parental support plays an important role in children's schoolwork motivation and may have been even more important during the first UK COVID‐19 pandemic lockdown because all schoolwork was completed at home. When examining the effect of parental support on children's schoolwork motivation, research has typically focused on comparing families with each other (i.e., difference between families). In reality, however, the effect unfolds as a transactional, bidirectional process between parents and children over time (i.e., a within family process). This research trend can result in imprecise conclusions about the association between parental support and schoolwork motivation. Objectives: We examined bidirectional effects of parental schoolwork support and children's schoolwork motivation at both the between‐family and within‐family level. Methods: This study reports findings from a weekly‐diary study conducted during the first UK COVID‐19 school lockdown. Cross‐lagged within and between multilevel modelling was used to analyse data from UK secondary school students ( N = 98) in Years 7–9. Results: Between‐family results show no evidence of association between motivation and parental support. Within‐family results indicate that higher motivation (assessed as higher expectations of success) predicted more support from parents. However, in contrast with predictions, weekly levels of parental support did not predict children's weekly fluctuations in motivation. Conclusions: Within‐family results were not consistent with between‐family results. This study is novel in showing that child‐driven effects appear to be important in eliciting parental support within families over time.